THE CORRELATION BETWEEN LEARNING STYLES AND PERCEIVED LISTENING COMPREHENSION OF ENGLISH DEPARTMENT STUDENTS - Rizky Gushendra; Rika Rahmi (Journal of English and Arabic Language Teaching, 2026)
The purpose of this study was to investigate the correlation between students’ learning styles and their perceived listening comprehension in the English Education Department at State Islamic University of Sultan Syarif Kasim Riau. This study was a quantitative correlational research. The sample consisted of 105 students selected by using a simple random sampling technique. In collecting the data, the researcher distributed two questionnaires to the respondents. The first questionnaire consisted of 30 items to identify students’ learning styles, while the second questionnaire consisted of 21 items to identify students’ perceived listening comprehension. The researcher used descriptive statistical analysis and Pearson Product-Moment Correlation through IBM SPSS Statistics version 25. The findings showed that visual learning style was the most commonly used learning style among the students. The Pearson Product-Moment Correlation analysis showed that the sig. (2-tailed) values for visual, auditory, and kinesthetic learning styles were 0.000, 0.001, and 0.003, respectively, which were lower than 0.05. In conclusion, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted, indicating that there was a significant positive correlation between students’ learning styles and their perceived listening comprehension.